Kinematics Research and Verification of Exoskeleton Robot for Upper Limb Rehabilitative - Li Jing; Cao Min (Jixie chuandong)
In order to achieve man-machine collaboration more closely and determine a reasonable and accurate model of upper limb movement,according to the anatomical structure of upper limb,a design eightsection upper limb exoskeleton rehabilitation robot is proposed. Based on the usual upper limb robot to make improvements,according to the complex structure of the upper limb to establish accurate equivalent kinematic model to achieve the robot and the internal structure of the shoulder joint alter accordance,and can alleviate the treatment of discomfort effectively. Then the reachable workspace of upper limb motion is simulated accurately.The simple inverse kinematics algorithm is used to solve each variable of joint. According to the characteristics of the human body,the rehabilitation trajectory planning is selected by the method of double-quaternion in task space and verified by SolidWorks,MATLAB and V-REP software. The rationality and feasibility of the design and algorithm is proved.